Zginanie Płyty w Kształcie Pierścienia Kołowego - Vodička, V. (Engineering Transactions, 1957)
Mathematical in character, this paper is also of practical importance.All equations for a circular ring subjected to bending by a load uniformly distributed over the region between the circles of radii and d (Fig. 1) are derived. Consideration is given to cases of simple support on the outer or inner edge. Arising out of the relatively general manner in which the problem is treated, the results obtained include certain matters important in engineering practice. All considerations are based on the familiar Kirchhoff assumptions that, (1), Hooke's law is valid, (2), the middle surface of the; plate undergoes no elongation during bending, and (3), the fibres normal to the middle surface of the plate before deformation remain normal to the deformed surface.